Sytuacja prawna nieruchomości służących zaspokajaniu potrzeb ludności miejskiej (próba podsumowania): [Legal status of real properties fulfilling the needs of urban population (a trial of summing up)] (Studia Prawnicze / The Legal Studies, 2023)
Summing up considerations presented in three previous papers the Author adds some thoughts concerning the problems omitted there (e.g. legal status of urban real properties situated beyond the scope of land designated for building purposes). He also gives his suggestions as to the new regulation and legal status of urban real properties designated for construction purposes and of summerhouse lots. Generally, the Author’s opinion of basic principles of such regulation is favorable but at the same time he also points out to the need of changes as far as some paricular solutions are concerned. According to the Author’s view several detailed solutions are too rigorous for the owners of real properties and do not guarantee the respect of their justified interests. In relation to summer-house lots the Author points out to the urgent need of regulating their legal status. The lack of such regulation causes many negative phenomena from the point of view of general interest as well as from the point of view of the interest of the growing number of citizens who wish to organize their individual recreation. Taking into consideration significant relation between the housing and recreation needs of urban population the Author suggests regulation of the problems of real properties designated for building purposes and those concerning summer-house lots in one normative act.